Design of STRAUS-R accelerator - Gordeev, V.S.; Myskov, G.A.; Mikhailov, E.S.; Laptev, D.V. (Вопросы атомной науки и техники, 2001)
The paper presents a design of the direct-operation high-current electron accelerator STRAUS-R that is a modification of STRAUS-2 now in force. The accelerator is aimed at generating single bremsstrahlung pulses in the mode of electron beam focusing on the target. According to the calculations it should provide for getting the dose (Si) of 0.2÷0.25 Gy at a 1 meter distance from the target, the electron beam current being equal to 50÷60 kA, boundary energy of electrons – to 2.7÷3.0 MeV, bremsstrahlung pulse duration – to ≤ 50 ns and beam diameter on the target – to ≤ 5 mm. The description and results of numerical simulation of physics processes taking place in the accelerator are given.